(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This comparative study explores the conceptualization of the "enclosed world" in Franz Kafka’s “The Trial” and Chingiz Aytmatov’s “The Scaffold”, focusing on thematic structure, genre, characterization, and literary devices and how the two authors construct psychological, social, and philosophical confinement. Although the texts emerge from distinct cultural, linguistic, and historical contexts, they both articulate the individual’s confrontation with systems of oppression-be it bureaucratic, existential, moral, or ideological. Through close textual analysis and contextual comparison, the research evaluates key themes such as guilt, justice, alienation, spiritual collapse, and the human quest for meaning. While Kafka foregrounds existential absurdity and the irrational mechanisms of power, Aytmatov emphasizes moral degeneration and spiritual responsibility within a collapsing socio‑ethical landscape. The study concludes that both authors depict a claustrophobic universe where human dignity is tested, yet they diverge in their philosophical orientation: Kafka portrays the futility of resistance within an incomprehensible system, whereas Aytmatov reveals the possibility of spiritual transcendence despite societal decay.